Effect of Work Discipline, Education and Training, and Incentives on Employee Performance Through Job Satisfaction at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak - Fajar Wahyu Hidayat; Sri Rahayu; Rifda Fitrianty (CV. Era Digital Nusantara, 2026)
This study aims to analyze the effect of work discipline, education and training, and incentives on employee performance through job satisfaction at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak. This research employed a quantitative approach with an explanatory research design. The respondents consisted of 194 employees. Data were collected using a questionnaire with a 1–5 Likert scale and analyzed using SEM-PLS. The results show that work discipline, education and training, and incentives have a positive and significant effect on job satisfaction. Work discipline, education and training, incentives, and job satisfaction also have a positive and significant effect on employee performance. In addition, job satisfaction is proven to mediate the effect of work discipline, education and training, and incentives on employee performance. These findings indicate that improving employee performance is not only directly determined by work discipline, education and training, and incentives, but also through the improvement of job satisfaction. Therefore, Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak needs to strengthen work discipline management, implement relevant education and training programs, improve an appropriate incentive system, and enhance employee job satisfaction to support more optimal employee performance.